High Frequency Resonance Frequency Shift Method for Cable Distribution System - Mingxing ZHU; Binbin KONG; Huaying ZHANG (Zhongguo dianli)
In order to solve the problem of high frequency resonance in cable distribution network, a high frequency resonance frequency shift method based on impedance reconstruction of distribution network is proposed. Firstly, an analysis is made of the mechanism of high frequency harmonic source and high frequency resonance in cable distribution network. Secondly, a high frequency resonance frequency shift method is proposed for impedance reconstruction of cable distribution network, and the frequency shift and resonance peak suppression effects are compared after reconstruction of different passive impedances. And then, based on actual project cases, the high frequency resonance suppression effects of the proposed method and its impact on the system stability are evaluated using the Bode diagram and root locus plotted with the system function, and the effectiveness of the proposed method is verified. Finally, the influence of passive impedance parameters on high frequency resonance of distribution network is studied.